Being the Father of a Preterm-Born Child: Contemporary Research and Recommendations for NICU Staff - Baldoni, Franco; Ancora, Gina; Latour, Jos M. (Frontiers in Pediatrics, 2021)
Background: Most studies on parental reactions to a preterm birth and to hospitalization of the newborn in Neonatal Intensive Care Units (NICUs) have involved mothers. However, emotional responses and behaviors of fathers are equally important. Usually, the father is the first to meet the preterm newborn, to find out information about baby’s condition and to communicate to the mother and other family members. In this context he is often left alone and can show psychological difficulties including affective disorders such as depression or anxiety. This paper describes the role of fathers in the NICU, the best practices to support fathers, and to explain the role of a psychologist in the NICU staff. Considerations and suggestions are provided on the difficulties encountered to support parents, with a focus on the role of fathers during the COVID-19 pandemic. Methods and Discussion: Considering contemporary research data and following an attachment perspective, we analyze the role of the father of a preterm-born child in the relation with the partner and in newborn caring. Research has shown that involving fathers in newborn care in NICU and at home is essential not only because it promotes the father/son attachment relationship and has positive effects on the psychological and somatic development of the newborn, but also for the health of the mother and whole family. Conclusion: Recommendations are provided to enhance the functions of fathers in the NICU, promote their involvement in the care of their infant, and interventions to prevent the manifestation of psychological suffering and/or perinatal affective disorders. The commitments of a psychologist in a NICU team are presented and require not only clinical skills, but also the ability to manage the emotional and relational difficulties of fathers, family and NICU staff. Considerations and suggestions are provided on the difficulties encountered by parents in the NICU during the COVID-19 pandemic.